Стабільні квазіпорядки на деяких переставних інверсних моноїдах - Дереч, В.Д. (Український математичний журнал, 2014)
Пусть G — произвольная группа биекций на конечном множестве. Обозначим через I(G) множество всех инъекций, каждая из которых включается в биекцию из G. Множество I(G) относительно обычной операции композиции бинарных отношений образует инверсный моноид. В данной статье изучаются различные свойства полугруппы I(G). В частности, установлены необходимые и достаточные условия для того, чтобы инверсный моноид I(G) был перестановочным (т. е. ξ○φ=φ○ξ для любой пары конгруэнций ξ,φ на I(G)), и в этом случае описана структура каждой конгруэнции на I(G). Приведено описание стабильных порядков на I(An), где An — альтернативная группа. Let G be an arbitrary group of bijections on a finite set. By I(G), we denote the set of all injections each of which is included in a bijection from G. The set I(G) forms an inverse monoid with respect to the ordinary operation of composition of binary relations. We study different properties of the semi-group I(G). In particular, we establish necessary and sufficient conditions for the inverse monoid I(G) to be permutable (i.e., ξ ○ φ = φ ○ ξ for any pair of congruences on I(G)). In this case, we describe the structure of each congruence on I(G). We also describe the stable orderings on I(A n ), where A n is an alternating group.